2000
DOI: 10.1577/1548-8659(2000)129<1196:eostap>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Suture Type and Patterns on Surgical Wound Healing in Rainbow Trout

Abstract: In two separate experiments we investigated the effects of different types of suture material and patterns on wound healing in rainbow trout Oncorhynchus mykiss with and without transmitter implants. We used absorbable and nonabsorbable monofilament and braided silk sutures in simple interrupted and vertical mattress patterns to close 3-cm incisions on rainbow trout. Braided silk sutures and vertical mattress suture patterns caused significantly more tissue inflammation (P Ͻ 0.05) as shown by macroscopic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 16 publications
(32 reference statements)
4
66
1
Order By: Relevance
“…Past studies have shown that technology, gear, species, fish handling, surgeon training, and environmental conditions are confounding factors, and thus hamper researchers' abilities to design future studies, develop standardized sampling protocols, and, most importantly, they can greatly affect biotelemetry and survival model assumptions (Wagner et al 2000;Welch et al 2007;McCormick et al 2009;Cooke et al 2011). The unifying tenet of these assumptions is that intra-coelomic implanted fish should have the same behaviors, survival rates, and physiological costs as un-implanted fish (Skalski 1998(Skalski , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that technology, gear, species, fish handling, surgeon training, and environmental conditions are confounding factors, and thus hamper researchers' abilities to design future studies, develop standardized sampling protocols, and, most importantly, they can greatly affect biotelemetry and survival model assumptions (Wagner et al 2000;Welch et al 2007;McCormick et al 2009;Cooke et al 2011). The unifying tenet of these assumptions is that intra-coelomic implanted fish should have the same behaviors, survival rates, and physiological costs as un-implanted fish (Skalski 1998(Skalski , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…During subsequent trips, acoustic transmitters were surgically implanted into the body cavity of each shark through a small (3 to 4 cm) incision on its ventral surface, just anterior to the pelvic fins. The incision was closed with monofilament sutures using a simple interrupted stitch (Wagner et al 2000). Transmitters were coated with a mixture of paraffin and candle wax to reduce possible immune response to the presence of a foreign body within the sharks.…”
Section: Methodsmentioning
confidence: 99%
“…Radio transmitters were surgically implanted in Dolly Varden using methods known to be appropriate and effective for salmonid fishes (Winter, 1996;Wagner et al, 2000;Jepsen et al, 2002). Transmitters weighed 10 g in air, were approximately 6 cm long and 1 cm in diameter, and trailed a whip antenna 40 cm long.…”
Section: Sample Selection and Tagging Protocolmentioning
confidence: 99%
“…The antenna was routed through a hole posterior to the pelvic girdle with a hypodermic needle and a grooved director in a modified shielded-needle procedure (Ross and Kleiner, 1982). The transmitter was placed into the peritoneum through the incision and closed with three monofilament sutures using a simple interrupted suture pattern (Wagner et al, 2000). After surgery, fish were held in freshwater to recover and released when they were able to swim away vigorously.…”
Section: Sample Selection and Tagging Protocolmentioning
confidence: 99%